Personalized Digital Smile Design for Predictable Aesthetic Results - Iliev Georgi (Balkan Stomatological Society, 2016)
Nowadays in the aesthetic dentistry concepts, techniques, and materials which aim is to establish new smiles with minimally invasive approaches and maximum natural effect on the restorations and in the same time to restore the mastication and phonetics for a better quality of life are used. However, the patient's demands and the level of information has driven the profession to a certain questioning respecting the treatment customization especially those related to treatment planning according to the individual psychological characteristics of each patient, that if ignored, may lead to esthetically dissatisfaction, even though all the esthetic rules which tend to establish standards were incorporated.